Réponses

  • Utilisateur Brainly
2014-09-28T21:39:09+02:00
1/(x-1) + 1/(x-9)  \leq  1/x \\
1/(x-1) + 1/(x-9) = 1/x \\
Avec \ \ x  \neq  1 \ ; x \  \neq  9 \  ; \  \neq  0 \\

1/(x-1) + 1/(x-9) - 1/x = 0 
[x(x-9)]/[x(x-1)(x-9)] + [x(x-1)]/[x(x-1)(x-9)] - [(x-1)(x-9]/[x(x-1)(x-9] = 0 
[(x²-9x)+(x²-x)-(x²-9x-x+9)]/[x(x-1)(x-9)] = 0

(x²-9x+x²-x-x²+9x+x-9)/[x(x-1)(x-9)] = 0
(x²-9)/[x(x-1)(x-9)] = 0

Un quotient est nul si et seulement si son numérateur est nul.

x² - 9 = 0
x² = 9
x = √9         
x = - 3     x = 3

S= {- 3 ; 3}

Tableau de signes :
                                                                                                                    
x                   - ∞                       - 3                         + 3                          + ∞   
x² - 9                           +             0            -               0                +                 

f(x) ≤ 0 dans [ - 3 ; 3]